An Efficient Neuro-framework for Brain Tumor Classification Using a CNN-based Self-supervised Learning Approach with Genetic Optimizations - Ravali, Paripelli; Reddy, Pundru Chandra Shaker; Praveen, Pappula (Current Neuropharmacology, 2025)
<span class=
Keywords: deep learning